Did Financial Consumers Benefit from the Digital Transformation? An Empirical Investigation and a Case Study - Park, Soojin; Cho, Man (KDI School of Public Policy and Management, 2021)
This study aims to document the inter-linkages between two on-going global trends through an empirical investigation – (1) the rapid advancement of the ICT-driven innovations in delivering various types of financial service, and (2) the growing legal and regulatory efforts to protect consumers in the financial markets, after the recent financial crisis in particular. To that end, we compile a set of macro-level indicators on the aggregate outcomes of the financial service sector in Korea during the last three decades, and conduct a regression analysis to gauge the effects of the digital transformation (DT) in the country on those indicators. Using an ARDL-ECM as our empirical model, our results show that: Over time, the unit cost for financial intermediation in the country tends to move in tandem with the growth of economic output, although the profit portion of the cost did not exhibit a long-term relationship with the GDP trend; The long-term effect of the DT trend is negative (i.e., costsaving) for labor input and capital expenditure, which are shown to be statistically significant, and, as a consequence, its impact on the total intermediation cost is also positive and statistically significant. Based on the above outcomes, we elaborate their implications in designing a set of policy instruments to protect financial consumers, and also discuss the Vietnamese case as an illustration to extend this type of macro-level analysis for the purpose of coming up with a policy regime for financial consumers in an emerging-market context.
Keywords: Digital Transformation; Financial Consumer Protection; Error Correction Model (ECM); Financial Consumer Policies